Studi Perbandingan Pengalaman Pengguna pada Platform E-Commerce Digital - Eka Desy Asgawanti; Angga Priyatna (Prodi Ilmu Komunikasi Fakultas Komunikasi & Desain Kreatif, 2026)
This study aims to analyze the comparative user experience of digital e-commerce platforms among students at the State Polytechnic of Creative Media. The approach used was quantitative with a comparative design, using a Likert-scale questionnaire measuring five key dimensions of user experience: price, ease of use, service quality, delivery speed, and promotions. The data obtained were analyzed using descriptive statistics and mean comparisons to identify differences in user experience across e-commerce platforms. The results indicate significant differences in user experience between platforms. Shopee excels in the dimensions of price, promotion, and delivery speed, while Tokopedia excels in service quality and ease of use. Lazada ranks relatively lower on most dimensions. These findings suggest that user experience is shaped by a combination of interacting factors, with promotion and price being the most dominant among students. This study contributes to the development of user experience studies in e-commerce through a comparative approach. Furthermore, the results also provide practical implications for e-commerce platform managers in designing strategies that are more oriented towards the overall user experience. By understanding differences in user experience across platforms, companies can improve service quality and competitiveness in an increasingly competitive digital ecosystem.